2023
DOI: 10.3390/polym15081915
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Interplay of Antimicrobial Properties and Cellular Response in Physically Crosslinked Hyaluronic Acid/ε-Polylysine Hydrogels

Abstract: The reduction of tissue cytotoxicity and the improvement of cell viability are of utmost significance, particularly in the realm of green chemistry. Despite substantial progress, the threat of local infections remains a concern. Therefore, hydrogel systems that provide mechanical support and a harmonious balance between antimicrobial efficacy and cell viability are greatly needed. Our study explores the preparation of physically crosslinked, injectable, and antimicrobial hydrogels using biocompatible hyaluroni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 65 publications
1
4
0
Order By: Relevance
“…Increasing the content of HA not only enhances the mechanical properties of HA-PL hydrogels, but also improves the cellular biocompatibility without exhibiting any cytotoxicity [46]. This finding is consistent with the research of Aunina [47]. Due to the large number of carboxyl and hydroxyl groups in the hyaluronic acid molecule, this allows hyaluronic acid to absorb exudates and enhance cell adhesion [55].…”
Section: Hyaluronic Acidsupporting
confidence: 82%
“…Increasing the content of HA not only enhances the mechanical properties of HA-PL hydrogels, but also improves the cellular biocompatibility without exhibiting any cytotoxicity [46]. This finding is consistent with the research of Aunina [47]. Due to the large number of carboxyl and hydroxyl groups in the hyaluronic acid molecule, this allows hyaluronic acid to absorb exudates and enhance cell adhesion [55].…”
Section: Hyaluronic Acidsupporting
confidence: 82%
“…Remarkable properties, such as biodegradability, heat stability, and water solubility along with a wide range of antimicrobial properties encourage the use of ε -PL in various industrial and pharmaceutical fields, including agriculture, food, chemistry, and biomedical [35]. In recent years, ε-PL has become a great candidate to use as suture or dressing material when conjugated with other biomaterials such as cellulose, hyaluronic acid, and chitosan due to its exhibited antimicrobial and antibiofilm ability without inducing an inflammatory response [36–40].…”
Section: Resultsmentioning
confidence: 99%
“…When PVA and EPL were added at the same time, the mechanical properties of BPE hydrogel prepared by adding PVA and EPL were reduced to a certain extent. The data show that when the strain reaches 85 %, no hydrogel breakage occurs, and the hydrogel can withstand a stress of 2.16 MPa, considering the effect of electrostatic interaction between EPL and BP [31,32] . The above data indicated that the prepared BPE hydrogel had excellent mechanical properties and could provide strong mechanical support for the application of wound dressing.…”
Section: Compression Testmentioning
confidence: 97%
“…As shown in Figure 5c, the addition of EPL can reduce the mechanical properties of BPE double network hydrogel, which may be caused by the electrostatic interaction between EPL and hydrogel network [31,32] . However, it can be seen from the figure that when EPL concentration reaches 5 %, the yield stress can still reach about 500 Pa, which ensures that the hydrogel can load more antibacterial substances and improve the antibacterial activity of the hydrogel.…”
Section: Rheological Characterizationmentioning
confidence: 99%
See 1 more Smart Citation